2021
DOI: 10.3389/fmicb.2021.748890
|View full text |Cite
|
Sign up to set email alerts
|

HigB1 Toxin in Mycobacterium tuberculosis Is Upregulated During Stress and Required to Establish Infection in Guinea Pigs

Abstract: The extraordinary expansion of Toxin Antitoxin (TA) modules in the genome of Mycobacterium tuberculosis has received significant attention over the last few decades. The cumulative evidence suggests that TA systems are activated in response to stress conditions and are essential for M. tuberculosis pathogenesis. In M. tuberculosis, Rv1955-Rv1956-Rv1957 constitutes the only tripartite TAC (Toxin Antitoxin Chaperone) module. In this locus, Rv1955 (HigB1) encodes for the toxin and Rv1956 (HigA1) encodes for antit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 102 publications
1
7
0
Order By: Relevance
“…These observations imply that MenT2 is essential for successful colonization or bacterial dissemination from the lungs to the spleens. Other mutant strains of M. tuberculosis, such as Δhbha, ΔrelA, ΔdevR, ΔhigB1 and ΔmymA, have shown similarly attenuated phenotypes [76,[78][79][80]. The tissue damage was similar in the spleens and lungs of guinea pigs infected with the parental and complemented strains.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…These observations imply that MenT2 is essential for successful colonization or bacterial dissemination from the lungs to the spleens. Other mutant strains of M. tuberculosis, such as Δhbha, ΔrelA, ΔdevR, ΔhigB1 and ΔmymA, have shown similarly attenuated phenotypes [76,[78][79][80]. The tissue damage was similar in the spleens and lungs of guinea pigs infected with the parental and complemented strains.…”
Section: Discussionmentioning
confidence: 89%
“…We have also previously reported that M. tuberculosis with individual deletion of either toxins or TA complexes are impaired for growth in animals [20, 23, 24, 27, 76]. However, the growth of the parental, Δ vapC28 , Δ vapC21 and ΔdarTG mutant strains was similar in animal tissues [20, 25, 77].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Typically, Type II modules are composed of a protein toxin and a cognate antitoxin protein that interact via protein-protein interaction (17). While several Type II systems have been evaluated in E. coli and M. smegmatis for their cytotoxicity (18)(19)(20)(21) others such as VapBC, MazEF, ParDE, RelBE and HigAB have been implicated in stress-induced survival of M. tuberculosis (19,(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…The TAC chaperone, which is homologous to the export chaperone SecB of E. coli 32,33 , specifically interacts with the C-terminal chaperoneaddiction region of the antitoxin to prevent its aggregation and degradation, and to facilitate subsequent inhibition of the toxin by the antitoxin [34][35][36] . Although transcription of TAC is induced under relevant stresses for M. tuberculosis, including nutritional starvation, hypoxia, antibiotics treatment, and drug-induced persistence 22,23,[37][38][39] , very little is known about its possible involvement in M. tuberculosis physiology and virulence 40 . Deletion of the HigA TAC antitoxin is lethal, possibly due to the synthesis of free active toxin 39 .…”
mentioning
confidence: 99%